2014
DOI: 10.1016/j.jastp.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based observations of the relations between lightning charge-moment-change and the physical and optical properties of column sprites

Abstract: Ground-based observations of the relations between lightning charge-momentchange and the physical and optical properties of column sprites. Optical observations of 66 sprites, using a calibrated commercial CCD camera, were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…Adachi et al (2004) analyzed 13 sprite events in winter thunderstorms over the Sea of Japan and reported a positive correlation between the CMC values and the numbers of sprite entities (R 2 = 0.45) and a higher correlation with the parent strokes' peak currents (R 2 = 0.9). More recently, Yaniv et al (2014) analyzed 26 events in winter thunderstorms in the Eastern Mediterranean and found a very weak correlation (R 2 = 0.15) with the CMC of the parent stroke. Fig.…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adachi et al (2004) analyzed 13 sprite events in winter thunderstorms over the Sea of Japan and reported a positive correlation between the CMC values and the numbers of sprite entities (R 2 = 0.45) and a higher correlation with the parent strokes' peak currents (R 2 = 0.9). More recently, Yaniv et al (2014) analyzed 26 events in winter thunderstorms in the Eastern Mediterranean and found a very weak correlation (R 2 = 0.15) with the CMC of the parent stroke. Fig.…”
Section: Data and Resultsmentioning
confidence: 99%
“…We did not perform a full dimensional analysis of the columns in this database (e.g. of their lengths and volumes occupied), however Yaniv et al (2014) analyzed a partial sample and reported a linear correlation between the sprite column's lengths and the CMC of the parent flash: stronger flashes produce longer columns, due to the larger quasi-electrostatic field that enables the propagation of sprite streamers to lower altitudes. With the benefits of high-speed imagery at 10,000 frames per second, Stenbaek-Nielsen and McHarg (2008) showed that in US summer thunderstorms, column (or C-) sprites are typically downward-only moving straight luminous features, while carrot sprites exhibit both downward and upward streamer movement, the latter forming the diffuse appearance on top, resembling the leaves of garden carrots.…”
Section: Morphological Distributionmentioning
confidence: 99%
“…The range of the present CMC values is similar to those reported by Hu et al [] for summer storms in U.S. plains or to that in van der Velde et al [] for storms in the South of Europe. However, it is larger than that in Matsudo et al [] for winter storms in Japan and that in Yaniv et al [] for winter storms observed during campaigns conducted from Israel. The HyLMA data allow analyzing several characteristics of most of these flashes, especially their duration, as reported in Table .…”
Section: Discussionmentioning
confidence: 99%
“…The background gray level (GL 0 ) is determined using two ROI parallel and outside of the streamer section with the same dimensions (solid boxes in Figure 2 (a)). A similar method to determine the background signal was used by Yaniv et al [45]. Several hundred streamer sections were analyzed in this manner at each pressure.…”
Section: Experimental Methodsmentioning
confidence: 99%